Evaluation of plasma angiopoietin‐2 and vascular endothelial growth factor in healthy dogs and dogs with systemic inflammatory response syndrome or sepsis. (21st December 2018) - König, Maya; Nentwig, Alice; Marti, Eliane; Mirkovitch, Jelena; Adamik, Katja‐Nicole; Schuller, Simone
Abstract : Background: Angiopoietin‐2 (Ang‐2) and vascular endothelial growth factor (VEGF) are regulators of endothelial permeability. Objective: Plasma concentrations of Ang‐2 and VEGF are increased in dogs with systemic inflammatory response syndrome (SIRS) and sepsis and are correlated with disease severity and outcome. Animals: Healthy dogs (n = 18) and client‐owned dogs with SIRS (n = 34) or sepsis (n = 25). Methods: Prospective observational study. Ang‐2 and VEGF concentrations in admission plasma samples were compared between healthy dogs and dogs with SIRS or sepsis, and between survivors and non‐survivors. Correlations with the acute patient physiologic and laboratory evaluation (APPLEfast ) disease severity score were examined. Results: Median Ang‐2 was significantly higher in dogs with SIRS (19.3; interquartile range [IQR]: 8.6‐25.7 ng/mL) and sepsis (21.2; IQR: 10.3‐30.1 ng/mL) compared to healthy dogs (7.6; IQR: 6.7‐9.8 ng/mL). Ang‐2 was significantly higher in non‐survivors (24.1; IQR: 11.9‐50.0 ng/mL) than survivors (10.2; IQR: 7.2‐21.5 ng/mL) but did not correlate with the APPLEfast score. Admission Ang‐2 predicted negative outcome in dogs with SIRS and sepsis with reasonable accuracy (area under the curve [AUC]: 0.75, confidence interval [CI]: 0.59‐0.85; sensitivity: 0.5, CI: 0.29‐0.71; specificity: 0.87, CI: 0.75‐0.95); differentiation between sepsis and SIRS was poor (AUC: 0.58). Plasma VEGF was significantly higher in dogs with sepsis (45; IQR: 14‐107.5 pg/mL) than in dogs with SIRS (3.3; IQR: 0‐35.6 pg/mL) or healthy dogs (0; IQR: 0 pg/mL; P = 0.008). VEGF was significantly ( P = .0004) higher in non‐survivors (34.5; IQR: 0‐105.7 pg/mL) than in survivors (0; IQR: 0‐55.2 pg/mL). The ability of VEGF to predict a negative outcome was poor. Conclusions and Clinical Importance: Ang‐2 may represent a useful additional prognostic marker in dogs with SIRS.